Novel Fluorinated Poly (Lactic-Co-Glycolic acid) (PLGA) and Polyethylene Glycol (PEG) Nanoparticles for Monitoring and Imaging in Osteoarthritis - Luana Zerrillo; Karthick Babu Sai Sankar Gupta; Fons A.W.M. Lefeber; Candido G. Da Silva; Federica Galli; Alan Chan; Andor Veltien; Weiqiang Dou; Roberta Censi; Piera Di Martino; Mangala Srinivas; Luis Cruz (MDPI AG, 2021)
Polymeric nanoparticles (NPs) find many uses in nanomedicine, from drug delivery to imaging. In this regard, poly (lactic-co-glycolic acid) (PLGA) and polyethylene glycol (PEG) particles are the most widely applied types of nano-systems due to their biocompatibility and biodegradability. Here we developed novel fluorinated polymeric NPs as vectors for multi-modal nanoprobes. This approach involved modifying polymeric NPs with trifluoroacetamide (TFA) and loading them with a near-infrared (NIR) dye for different imaging modalities, such as magnetic resonance imaging (MRI) and optical imaging. The PLGA-PEG-TFA NPs generated were characterized in vitro using the C28/I2 human chondrocyte cell line and in vivo in a mouse model of osteoarthritis (OA). The NPs were well absorbed, as confirmed by confocal microscopy, and were non-toxic to cells. To test the NPs as a drug delivery system for contrast agents of OA, the nanomaterial was administered via the intra-articular (IA) administration method. The dye-loaded NPs were injected in the knee joint and then visualized and tracked in vivo by fluorine-19 nuclear magnetic resonance and fluorescence imaging. Here, we describe the development of novel intrinsically fluorinated polymeric NPs modality that can be used in various molecular imaging techniques to visualize and track OA treatments and their potential use in clinical trials.